Unraveling the role of active hydrogen caused by carbonyl groups in surface-defect passivation of perovskite photovoltaics. (15th June 2022) - Shi, Yi-Ran; Wang, Kai-Li; Lou, Yan-Hui; Zhang, Ding-Bo; Chen, Chun-Hao; Chen, Jing; Ni, Yu-Xiang; Öz, Senol; Wang, Zhao-Kui; Liao, Liang-Sheng
Abstract: The molecules with carbonyl group are regarded as ideal candidates to passivate surface-defects on metal halide perovskites. However, as an electron-withdrawing group, the CO groups are the ones that make hydrogen active on their adjacent atoms. Therefore, carbonyl compounds tend to produce keto-enol tautomerism and dissociation of hydrogen, which would affect their passivation effect. Herein, we chose three carbonyl-based molecules, morpholine, 3-morpholone and 3, 5-morpholone with different amounts of carbonyl groups, to systematically investigate the effect of active hydrogen on their defect-passivation effect. The passivation effect of multifunctional molecule would be maximized when the molecule was in an optimal configuration with negligible active hydrogen. Consequently, a champion power conversion efficiency of 23.05% was approached with 3-morpholone surface treatment. The finding in this work reveals the importance of carbonyl distribution in molecular configuration when designing multifunctional passivation molecules in perovskite photovoltaics. Graphical Abstract: ga1 Highlights: The presence of carbonyl group would greatly affect the passivation process of adjacent groups in surface-treatment effect. We demonstrated the importance of the distribution of carbonyl groups in molecular configuration. The adjacency of electron absorbing groups with other functional groups should be avoided as far as possible. We propose new consideration for future molecular design of passivation candidates in perovskite photovoltaics.